Production and characterization of silver nanoparticles supported on cotton fibers (Superficies y Vacío, 2013)
In this work, silver nanoparticles biocomposite by using cotton fiber as support and Camellia sinensis as reducing agent were prepared. For biocomposite preparation, anionically charged cotton fibers were first immersed in a silver ions solution. Later, a second immersion of the fibers in a Camellia sinensis solution was done. The biocomposites were characterized by infrared spectroscopy in order to identify structural changes of cellulose. The fibers were observed in Field Emission Scanning Electron Microscopy (FE-SEM) and Field Emission Transmission Electron Microscopy (FETEM) in order to determine the surface impregnation of the fibers with Ag nanoparticles and the grain size distribution respectively, finding average sizes of 5 y 11 nm for two different probes. Finally, the binding energies of the reduced silver as measured by X-ray photoelectron spectroscopy (XPS) show that metallic silver (Ag0) and a complex of silver and oxygen (Ag-O) were presented on the fibers.